2004
DOI: 10.1097/00001432-200406000-00003
|View full text |Cite
|
Sign up to set email alerts
|

How do viral infections predispose patients to bacterial infections?

Abstract: Respiratory viral infections may facilitate secondary bacterial infections and increase host immunopathology through the overproduction of inflammatory cytokines. Preventive measures, including vaccination and aggressive antimicrobial therapy early in the course of infection, may significantly reduce the morbidity and mortality of sepsis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
128
0
5

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(135 citation statements)
references
References 45 publications
0
128
0
5
Order By: Relevance
“…A temporal association between bacterial and viral infections is often observed in the human upper respiratory tract [71,72]. Infection by opportunistic colonizers, including Haemophilus influenzae and Moraxella catarrhalis, increases considerably following influenza and/ or respiratory syncytial virus (RSV) infections [71,72].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A temporal association between bacterial and viral infections is often observed in the human upper respiratory tract [71,72]. Infection by opportunistic colonizers, including Haemophilus influenzae and Moraxella catarrhalis, increases considerably following influenza and/ or respiratory syncytial virus (RSV) infections [71,72].…”
Section: Discussionmentioning
confidence: 99%
“…Infection by opportunistic colonizers, including Haemophilus influenzae and Moraxella catarrhalis, increases considerably following influenza and/ or respiratory syncytial virus (RSV) infections [71,72]. COPD is often associated with viral infections, mostly by rhinovirus, and it was recently shown that these infections indeed precipitate secondary bacterial infections, particularly in COPD patients [73].…”
Section: Discussionmentioning
confidence: 99%
“…Several reports indicate that changes due to virus in the respiratory tract prime the upper airway and lung make way for subsequent bacterial infection. Super bacterial infections are accompanied by virus-induced cytopathology, leading to immunological impairment, which could be caused in part by the overproduction of inlammatory cytokines [63]. Transformation of the immune response by curtailing the capacity of the host to clear bacteria may contribute to the severity of the resulting infection [64].…”
Section: Adjuvant Therapy To Treat Secondary Bacterial Superinfectionmentioning
confidence: 99%
“…Viruses facilitate bacterial infection through direct damage to the respiratory tract and indirect modulation of inflammatory pathways [19]. Analysis of bacteriologic and histopathologic data from the 1918-1919 influenza pandemic indicates that the majority of influenza-related deaths from that period resulted from secondary bacterial pneumonia [20‱].…”
Section: Co-infection With Viruses and Bacteriamentioning
confidence: 99%